Incidence, characteristics and management of recently diagnosed, microscopically invasive breast cancer by receptor status: Iowa SEER 2000–2013 - Thomas, Alexandra (Am J Surg, 2016)
BACKGROUND: Recent incidence, treatment patterns and outcomes for node negative microscopically invasive breast cancer (MIBC) have not been reported. METHODS: State Health Registry of Iowa data identified women with ductal carcinoma in situ (DCIS), MIBC, and Stage I breast cancer excluding MIBC (Stage 1BC). RESULTS: From 2000–2013, 1,706, 193 and 4,514 women were diagnosed with DCIS, MIBC and Stage 1BC, respectively. MIBC increased at an annual percentage change of 2.1 (p=0.041). MIBC was more frequently human epidermal-growth-factor-receptor-2 positive than Stage 1BC (39.7% vs 9.6%, p<0.001). Mastectomy was performed more frequently in MIBC than DCIS (40.9% vs 30.6%, p=0.014) or Stage 1BC (40.9% vs 33.8%, p=0.119). Chemotherapy was given to 4.1% of women with MIBC. Survival for women with MIBC was intermediate between DCIS and Stage 1BC. CONCLUSIONS: Management of MIBC is an increasingly frequent clinical scenario. Women with MIBC receive more aggressive local and systemic therapy than women with DCIS.